2022
DOI: 10.4000/chinaperspectives.13520
|View full text |Cite
|
Sign up to set email alerts
|

“A New Job after Retirement”: Negotiating Grandparenting and Intergenerational Relationships in Urban China

Abstract: Based on interviews with 120 adult only children and their parents in urban Tianjin, this article shows how grandparenting becomes a crucial site for the intergenerational negotiation around childcare, family obligations, and the unfulfilled aspirations for individualisation. While only child couples rely heavily on their parents for childcare, a lot of tensions are involved in this process. Although grandparents do not always willingly embrace the heavy burden of intergenerational childcare, their concern abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Recent research suggests a transition taking place within Chinese society with regard to grandparent childcare duties and expectations. Grandparents are speaking out about the “heavy burden” of taking care of grandchildren rather than accepting it as “a natural family obligation,” and they are also indicating a desire for a greater range of lifestyle choices for themselves (Lin & Mao, 2022, p. 54).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests a transition taking place within Chinese society with regard to grandparent childcare duties and expectations. Grandparents are speaking out about the “heavy burden” of taking care of grandchildren rather than accepting it as “a natural family obligation,” and they are also indicating a desire for a greater range of lifestyle choices for themselves (Lin & Mao, 2022, p. 54).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they have argued that family relationships and responsibilities are not constrained by the nuclear family boundary and highlighted the 'new forms of connectedness and embeddedness' of nuclear families within extended families and even broader social networks (Gilding, 2010: 763;Miller, 2017;Qi, 2021;Widmer and Jallinoja, 2008). Therefore, there is a need for further exploration of parental daily practices and their fluid connections, ongoing negotiations and interactions with grandparents or extended family over childcare, rather than sticking to static parental roles or family structures (Lin and Mao, 2022;Miller, 2017;Qi, 2021).…”
Section: Parenting As Interactive and Relational Practicesmentioning
confidence: 99%
“…Mr Jiang described his family collaboration as follows: Mr Jiang also reported that his mother joined the childcare team in April 2020. With the support of bilateral grandparents (Lin and Mao, 2022;Qi, 2021), Mr Jiang found that childcare responsibilities were easily shared. In some families, the couples also relied on other relatives' support in childcare.…”
Section: Extended Family Collaboration In Childcarementioning
confidence: 99%
See 2 more Smart Citations